(3GdEbfGY aj Md CdaGX CHj TLGYs - (3GdTQHjfj GdeUQj GdTGaYj, TeS GdOjf (B- (3GdNWjH, eMeO Hf CMeO, J (B977 (3g`s ((3UGHQ Hf TMGJg GdgdGhj GdTGaYjs)
(3ChdgG (B:s
(3HYO GdHSedI ; hgh MSHj hfYe Gdhcjd GdMeO ddg GdPj fTQ ddYdeGA CYdGeG hHYO ajbhd abjQ QMeg Gddg eMeO GdTQHjfj GdNWjH Cf eNJUQ GdEeGe CMeO Hf GdMSjf GdCUagGfj GdTgjQ HCHj TLGY hSejJg GdEbfGY aj Md CdaGX CHj TLGYs
(3BNQgG (B:s
(3hdG jdReg CLQI GdJWQjR dCf GdJWQjR jRjO bjeI GdKhH ZGdHG hdG cPdc GdcJGHI aEfgG bO JfbUgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 6s
(3eYLe GdeDdajf (B3 / 69s
(3EjVGM Gdecfhf (B2 / 448s
(3TPQGJ GdPgH (B8 / 384s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs